Candida and Candidiasis - Askun, Tulin (IntechOpen, 2023)
This book collates up-to-date information about Candida and candidiasis, covering the following topics: diversity and genetic structure of the genus Candida, invasion biology of candidiasis, pathogenicity, drug resistance, antifungal susceptibility, antifungal-resistant Candida strains, antifungal-resistant genes among resistant isolates, molecular mechanisms of antifungal resistance, diagnosis and targeted therapy of candidiasis, cytotoxicity, biofilms, Candida albicans and non-C. albicans, Covid-19 patients and proteomics, pustules, systemic therapies, topical therapies, new effective compounds against Candida spp. cutaneous candidiasis, oropharyngeal candidiasis, oesophageal candidiasis, vulvovaginal candidiasis, intestinal candidiasis, invasive candidiasis, molecular methods in the diagnosis of Candida strains, host-pathogen interactions, interactions between Candida and cancer, antifungal drug discovery, natural compounds effective against Candida strains, and novel active compounds for candidiasis treatment.